Psychometric validation of the Slovenian version of the Revised Child Anxiety and Depression Scale - child and parent versions (RCADS and RCADS-P) - Petrič, Mojca (Zdravstveno varstvo, 2024)
Objective: Anxiety and depression are common disorders in children and adolescents and can have a negative impact on their lives. The Revised Child Anxiety and Depression Scale – Child and Parent versions (RCADS and RCADS-P) are widely used standardized measurement tools, but the Slovenian versions have not yet been validated. The aim of the present study was to examine the psychometric properties of the Slovenian version of RCADS and RCADS-P in a representative Slovenian school sample. Methods: We examined the psychometric properties (factor structure, internal reliability, short-term stability, inter-rater agreement and convergent validity) of the Slovenian version of the RCADS and the RCADS-P in 754 primary and secondary school students and parents of 485 students. The short-term stability of anxiety and depressive symptoms in youth was assessed in a subsample of 117 children and adolescents. Results: Confirmatory factor analysis showed an acceptable fit of the 6-factor model with CFI=0.92, TLI=0.92 and RMSEA=0.056 for RCADS and with CFI=0.93, TLI=0.92 and RMSEA=0.047 for RCADS-P. Cronbach’s ? and McDonald’s ? ranged from 0.70 to 0.95 for the total scale and the six subscales. The subscales correlated significantly positively with the total Child Anxiety Life Interference Scale score. Conclusion: The results affirm the good psychometric properties of the Slovenian versions of RCADS and RCADS-P within a school-based sample. There is a need in the future to examine psychometric properties in clinical samples and to provide normative data.
Keywords: adolescents; anksiozne motnje; anxiety; children; depresije; depression; mladostniki; otroci; psihometrične lastnosti; psychometric properties; RCADS; RCADS-P